The Correlation Between the Husband's Support and the Psychological Well-Being of Pregnant Adolescents - Zike Zahrifa; Reni Purwo Aniarti (UM Purwokerto Press, 2022)
Background: Teenage pregnancy can be defined by the occurrence of pregnancy in girls aged 10-19 years who still have emotional instability. This emotional instability can affect the psychological well-being of pregnant adolescents, which will cause disturbances in their pregnancy; therefore, the husband's support is needed so that mothers can feel security and comfort in their pregnancy to achieve maternal and fetal health in the womb. Objective: To determine the correlation between husband's support and psychological well-being in pregnant adolescents. Method: This study used a quantitative method with a cross-sectional design. The sampling technique used total sampling with a total sample of 30 respondents. The study was conducted in the Moga Health Care Center Pemalang Regency, Central Jawa Province, Indonesia. Data analysis used is univariate analysis to determine the frequency distribution of respondent characteristics (age, number of pregnancies and education), and bivariate analysis to determine the relationship between independent variables (husband's support) with the dependent variable (psychosocial condition of adolescent pregnant women) Results: This study shows a significant correlation between husband's support and the psychological well-being of pregnant adolescents in the Moga Community Health Care Center, with a p-value of 0.000. Conclusion: Pregnant women who lack a husband's support will be at risk of experiencing psychological well-being in their pregnancy, especially pregnant adolescents.